Ethnicity and Prejudice: A Historical Shift - Acharya, Pradeep (Dhaulagiri Journal of Sociology and Anthropology, 2011)
The paper principally aimed to present a brief overview of the historical shift on the notion of ethnicity and prejudice around the wider global context with particular focus on local Nepalese context has solely based on the secondary information obtained from the review of pertinent literatures on ethnicity. The genesis of the approaches to ethnicity comprises some conceptual idea on ethnicity regarding its emergence and usage as a term in the social sciences. Ethnicity can be said to be very closely interlinked with prejudice in policy and practice at the level of individual, society and the state. The historical evidence suggests that there has been a gradual shift on the notion of both ethnicity and prejudice around different places at different time periods. In addition, it does contain significant research problems, which, can surely be elaborated, and its full significance drawn. Keywords: Ethnicity; prejudice; boundaries; social constructionist model; multilevel theory DOI: 10.3126/dsaj.v4i0.4514 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.85-98